Genetic Counseling: A Pathway to Understanding and Managing Inherited Health Risks - Praveen Basavaraj Katti; Poonam; Rangappa S. Ashi (International Journal of Evidence Based Nursing And Practices, 2026)
Genetic counseling is an essential aspect of personalized medicine that supports individuals and families in understanding the implications of inherited health conditions. With the rising prevalence of genetic disorders and advancements in genomic technologies, counseling provides critical insights into risk factors, diagnostic options, and informed decision-making. This paper explores the classification of genetic disorders, major genetic and environmental causes, and the expanding role of genetic counseling within India’s culturally diverse population. Key issues addressed include access disparities, community awareness, and the role of student nurses in advocacy and education. The manuscript emphasizes current developments in gene therapies, the integration of AI in diagnostics, and ethical considerations. A hypothetical case scenario has also been presented to reinforce how counseling supports decision-making. This comprehensive overview aims to advocate for genetic literacy, support healthcare providers, and reinforce the importance of equitable access to genetic counseling services across India.
Keywords: CRISPR; Ethical issues; Gene therapy; Genetic counseling; Genomic Medicine; India; Risk assessment; inherited disorders; student nurses